Ecofisiologia de Psychotria colorata em uma floresta sazonal semi - estacional - Alves, Magnólia Martins (2020)
Ecophysiological studies in the context of understory species have been widely discussed in order to describe and understand the ecophysilogical responses of plants in different types of environment. Given the importance of understory species, evaluate the composition of the soil seed bank and the natural regeneration of an area in an open rainforest. (Article 1) is to evaluate possible changes in gas exchange functioning in individuals of P. colorata in the understory in an open ombrophilous forest remnant due to seasonality (Article 2). In chapter 1, the evaluation of natural regeneration of seedlings of P. colorata was made, in terms of height, diameter of the base and number of leaves. The results indicated that the height classes, individuals fell into only two height classes, with the highest frequency observed in class I - from 20 to 40 cm [(138 followed by class II - 40 to 60 cm 92 individuals)] . As for the seed bank experiment, the germination of 84 individuals belonging to 11 families was recorded during the entire study (October 2017 to December 2018). The Fabaceae family (3) found the highest number of species, followed by Asteraceae (6), with 2 undetermined rates. In article 2, influence of seasonal variation on the ecophysiology of Psychotria colorata). For that, morpho-anatomical characteristics were investigated. It aimed to evaluate possible changes in gas exchange functioning in individuals of P. colorata in the understory in an open ombrophilous forest remnant depending on seasonality. At the Mata do Pau-Ferro Ecological Reserve located in the municipality of Areia, Paraíba, Brazil. Photosynthesis rate (A) (µmol m-2 s-1), stomatal conductance (Gs), transpiration (E) and internal carbon concentration (Ci) were measured. From the data obtained from these variables, the instantaneous efficiency of water use (USA, A/E) and instantaneous carboxylation efficiency (EiC, A/Ci) were calculated. Stomatal density was performed in the basal, median and apical part, numbers of trichomes, thickness of the adaxial and abaxial surfaces of the epidermis. The results obtained showed that the transpiration rate (E) was high in the months of greatest water availability, thus, the stomatal conductance (Gs) in April resulted in a value of 0.181 mol m-2 s -1, with greater precipitation. Stomatal density on the adaxial and abaxial sides of the leaves of Psychotria colorata increased in the months of low rainfall (average 110 stoma mm-2, 143 stoma mm-2, 97 stoma mm-2, 101 stoma mm-2). The seasonality effects of Psychotria colorata express the regenerative or adaptive success of the forest area.